Visualizing morphological principles for efficient photocurrent generation in organic non-fullerene acceptor blends - Köntges, Wolfgang; Perkhun, Pavlo; Kammerer, Jochen; Alkarsifi, Riva; Würfel, Uli; Margeat, Olivier; Videlot-Ackermann, Christine; Simon, Jean-Jacques; Schröder, Rasmus R.; Ackermann, Jörg; Pfannmöller, Martin (Energy & environmental science, 2020)
The efficiency of organic solar cells with donor polymers and non-fullerene acceptors depends on a complex morphology. Similar chemical and electronic structures impede generating in-depth insights in morphological details. We visualise molecular arrangements and the nanomorphology in PBDB-T:ITIC blends by correlating transmission electron micrographs and material distribution maps. Material phases are identified by machine learning on hyperspectral data from electron spectroscopic imaging. We observe a specific polymorph of ITIC after thermal annealing. During annealing, enhanced by the presence of additives, PBDB-T acts as nucleation site for ITIC due to strong pi-pi-interactions of the electron withdrawing groups of both molecules. This leads to efficient charge transport paths in ITIC phases with direct pi-pi-contact to PBDB-T at the interface. We conclude that pi-pi-stacking between donor and acceptor molecules facilitates charge carrier generation within mixed interface regions.
Gesehen am 18.06.2020